2012
DOI: 10.1208/s12249-012-9809-0
|View full text |Cite
|
Sign up to set email alerts
|

A Cremophor-Free Self-Microemulsified Delivery System for Intravenous Injection of Teniposide: Evaluation In Vitro and In Vivo

Abstract: In order to tackle the problems on low water solubility of teniposide, involvement of toxic surfactant in its injection, and the poor stability during infusion, a Cremophor-free teniposide self-microemulsified drug delivery system (TEN-SMEDDS) was prepared for the first time, characterized, and evaluated in comparison with teniposide injection (VUMON) in vitro and in vivo. The optimized formulation contained N, N-dimethylacetamide, medium-chain triglyceride, lecithin, and dehydrated alcohol besides teniposide.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Previous pharmacokinetic and tissue distribution study indicated that the effective of TEN-SMEDDS for the treatment of brain tumors may have no significant difference compared to VUMON, or was better (He, Cui et al 2012). The pharmacodynamic study illustrated that TEN-SMEDDS had the potency of antitumor.…”
Section: In Vivo Antitumor Measurementmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous pharmacokinetic and tissue distribution study indicated that the effective of TEN-SMEDDS for the treatment of brain tumors may have no significant difference compared to VUMON, or was better (He, Cui et al 2012). The pharmacodynamic study illustrated that TEN-SMEDDS had the potency of antitumor.…”
Section: In Vivo Antitumor Measurementmentioning
confidence: 97%
“…The total teniposide in the formed emulsion was detected through breaking the emulsion with 10 times of methanol and then analyzed by HPLC method (He, Cui et al 2012).…”
Section: Drug Loading Capacity and Entrapment Efficiency Of Ten-smeddsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to attain adequate bioavailability of poorly soluble drugs, special formulation strategies are employed to increase their dissolution in aqueous medium [2]. Traditionally, organic solvents are used as co-solvents [3] or a part of emulsion [4] to formulate the poorly soluble drugs as aqueous dosage forms. Alternatively, the drug is fitted in cyclodextrins, which have a hydrophobic interior and a hydrophilic exterior, and made soluble in water [5].…”
Section: Introductionmentioning
confidence: 99%